2022
DOI: 10.25157/teorema.v7i1.7002
|View full text |Cite
|
Sign up to set email alerts
|

Peramalan Pertumbuhan Ekonomi Provinsi Bengkulu Menggunakan Single Moving Average, Single Eksponential Smoothing Dan Ensemble

Abstract: Pertumbuhan ekonomi Provinsi Bengkulu sangat penting untuk diperhatikan karena Provinsi Bengkulu merupakan termiskin di Pulau Sumatra pada tahun 2019. Pertumbuhan ekonomi dapat dilihat dari YoY PDRB ADHK (%) setiap triwulan yang dipublikasikan oleh BPS Provinsi Bengkulu. Analisis data pada penelitian ini bertujuan melakukan peramalan dengan menggunakan teknik pemulusan yang cocok: Single Moving Average (SMA), Single Eksponential Smoothing (SES) dan Ensemble kedua pemulusan tersebut. Peramalan SMA, SES dan Ense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…For example, in some previous research has been done by combining other methods, among others: Previous research has combined other methods such as the comparison of ARIMA Box Jenkins forecasting with ARIMA ensemble (Tasyah et al, 2023). Other research on economic growth forecasting involves 3 methods Single MA, Single Exponential and ensemble (Fransiska, 2022). And finally another study, comparing ARIMA, GSTAR, ensemble stacking, and ensemble averaging found that the ensemble method produced the lowest RMSE value in rainfall forecasting (Anggraeni et al, 2018).…”
Section: Arima and Arimaxmentioning
confidence: 99%
“…For example, in some previous research has been done by combining other methods, among others: Previous research has combined other methods such as the comparison of ARIMA Box Jenkins forecasting with ARIMA ensemble (Tasyah et al, 2023). Other research on economic growth forecasting involves 3 methods Single MA, Single Exponential and ensemble (Fransiska, 2022). And finally another study, comparing ARIMA, GSTAR, ensemble stacking, and ensemble averaging found that the ensemble method produced the lowest RMSE value in rainfall forecasting (Anggraeni et al, 2018).…”
Section: Arima and Arimaxmentioning
confidence: 99%
“…Selain itu, pemilihan metode peramalan juga pernah dilakukan terhadap pertumbuhan ekonomi Provinsi Bengkulu. Pada penelitian ini metode yang dibandingkan adalah Single Moving Average, Single Exponential Smoothing, dan Ensemble dengan hasil Single Moving Average ialah metode yang terbaik [11].…”
Section: Pendahuluanunclassified